(3eNJUQ MGWH djds - (3Jbj GdOjf jMji Hf eMeO Hf jhSa GdSYjOj, GHf GdcQeGfjs; (3GHf CHj MLdI , CMeO Hf jMji Hf CHj HcQ GdJdeSGfj, TgGH GdOjf CHh GdYHGS,J (B776 (3g` s ((3eMeO EHQGgje GdYfGfj s)
(3ChdgG (B:s
(3bGd GHf Ybjd GdMfHdj aj cdGe LQi ef YGde Ydi hLg GdSNW hjRGMece Cgd GdTHg hGdHgQLg s
(3BNQgG (B:s
(3ONd eUQ ef GdCfHjGA EHQGgje hESeGYjd hjYbhH aGdJbWJ gPg GdahGFO hGdfcJ hCVaJ EdjgG s
(3fSNI KGfjIs
(3gj GdLRA GdKGfj ef GdfSNI GdChdi faSgG GdCRgQjI (B6900 (3CHGXI (B295s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs